Limb apraxia and the “affordance competition hypothesis” - Rounis, Elisabeth; Humphreys, Glyn (Frontiers in Human Neuroscience, 2015)
Limb apraxia, a disorder of higher order motor control, has long been a challenge for clinical assessment and understanding (Leiguarda and Marsden 2000).The deficits originally described in limb apraxia (Liepmann 1908) have been classified by the nature of the errors made by the patients leading to, namely, ideational and ideomotor apraxia. The dual stream hypothesis (Goodale and Milner 1992) has been used to explain these categories: ideational apraxia is thought to relate to a deficit in the concept of a movement (coded in the ventral stream), whereas ideomotor apraxia, is thought to arise from problems in the accurate implementation of movements within the dorsal stream. One of the limitations on understanding apraxia is the failure by the clinical literature to draw on knowledge of the factors determining actions in the environment. Here we emphasize the role of affordance. There is much recent work indicating that our responses to stimuli are strongly influenced by the actions that the objects ‘afford’, based on their physical properties and the intentions of the actor (e.g, Ellis & Tucker, 1998; Humphreys et al., 2010). The concept of affordance, originally suggested by Gibson (1979) has been incorporated in a recent model of interactive behaviour that draws from findings in non-human primates, namely the ‘affordance competition hypothesis’ (Cisek 2007). This postulates that interactive behaviour arises by a process of competition between possible actions elicited by the environment. In this paper we argue that ‘affordance competition’ may play a role in apraxia. We review evidence that at least some aspects of apraxia may reflect an abnormal sensitivity to competition when multiple affordances are present (Riddoch et al., 1998) and/or a poor ability to exert cognitive control over this competition when it occurs. This framework suggests a new way of conceptualising deficits in apraxia which invites further investigations in the field.